Reading Among Students: A Study Using a Modified Version of the Snowball Method - Dragan, Irina-Maria; Isaic-Maniu, Alexandru; Grigore, Ana-Maria (Advances in Social Sciences Research Journal, 2023)
The reading crisis is a real phenomenon of the last few years, the fondness for reading is free falling, and the lack of interest is reflected in the increasingly poor results in the national evaluations of schoolchildren. In the long term, the effects of the lack of reading reflect on the quality of human resources, including the area of cultural intelligence. The Romanian authorities have initiated measures to stimulate reading, but the results are still modest. The research undertaken by us aimed at evaluating the duration of time allocated to reading by students of the 5th-8th grades from a college in Bucharest, for which purpose the snowball method was used after having applied our original development that allows the completion of the research under conditions of quantitative criteria and the evaluation of decision errors. The snowball procedure in its classic version not only has advantages but also numerous inconveniences, of which the most important is the ambiguity regarding the volume of the investigated sample, because the number of interviewees cannot be predetermined, since it is dependent on the researcher’s decision to stop the investigation at a given moment or not. The solution proposed by the authors was to develop the sequential Wald test for the case of measurable characteristics, and the results obtained have a deeply original nature and can contribute to a great extent to the improvement of sociological research methods.